Embodied carbon emissions induced by the construction of hydropower infrastructure in China. (February 2023) - Ge, Zewen; Geng, Yong; Wei, Wendong; Jiang, Mingkun; Chen, Bin; Li, Jiashuo
Abstract: China has the largest installed hydropower capacity in the world, contributing more than 60% of the national renewable energy supply. In order to respond to climate change, China has constructed many hydropower projects during the past few decades. However, such large scaled infrastructure construction induced a large amount of embodied carbon emissions since many energy-intensive products were consumed. This study aims to account such embodied carbon emissions generated by the construction of hydropower infrastructure in China for a period of 2006–2015 by applying a hybrid method. The results show that the cumulative embodied carbon emissions from conventional hydropower projects and pumped-storage hydropower projects were 1.73E+08 tons and 1.40E+07 tons CO2 respectively. These embodied carbon emissions were mainly generated from construction engineering, electrical equipment, land expropriation and resettlement. Sichuan, Hubei, and Yunnan ranked the top three in terms of such embodied carbon emissions IEA, 2015, while Qinghai had the highest per capita embodied carbon emission. Guangdong and Zhejiang had the largest embodied carbon emissions from pumped storage hydropower projects. Installed capacity scale, location, and input field are three key influential factors on embodied carbon emissions. Finally, several policy recommendations are proposed to help mitigate such embodied carbon emissions by considering the Chinese realities. Highlights: Cumulative embodied carbon emissions from hydropower projects are accounted. Embodied carbon emissions were mainly generated from construction engineering. Sichuan, Yunnan, and Hubei had the most embodied carbon emissions from such projects. Installed capacity scale, location, and input field are key factors. Policy recommendations are proposed to help mitigate embodied carbon emissions.